James Clarke journal - Clarke, James, 1787-
Journal (1843 September 13-1845 October; 86 pages) of James Clarke of Boston while traveling in Australia. Includes comments on sheep herding, cattle drives, aborigines, and life in the Maitland and Sydney areas in New South Wales.
Negative photocopy.
Collection material in English.
Keywords: Cattle drives -- Australia; Indigenous peoples -- Australia; Sheepherding -- Australia; Australia -- Description and travel; Australia -- Social life and customs; Maitland (N.S.W.) -- Description and travel; Maitland (N.S.W.) -- Social life and customs; Sydney (N.S.W.) -- Description and travel; Sydney (N.S.W.) -- Social life and customs